Arctic Exceptionalism’ or ‘comprehensive security’? Understanding security in the Arctic - Hoogensen Gjørv, Gunhild; Hodgson, Kara Kathleen (Arctic Portal, 2019)
Source at https://arcticyearbook.com/images/yearbook/2019/Scholarly-Papers/11_AY2019_Hoogensen_Hodgson.pdf . Journal home page page https://arcticyearbook.com/arctic-yearbook/2019 . Since Mikhail Gorbachev’s icebreaking Murmansk speech in 1987, the Arctic has been considered to be an “exceptional” region of peace and cooperation in security studies. While acknowledging the relevance of this narrative, this article nevertheless argues the “Arctic exceptionalism” narrative is insufficient for understanding the complex security situation in the region. The lens of comprehensive security allows for an analysis of power that reveals which security narratives dominate, why, and who decides. After a brief description of the key elements associated with “Arctic Exceptionalism” and clarification of the terms “Arctic,” “security,” and “comprehensive security,” this article offers four core arguments against the dominance of the Arctic Exceptionalism narrative, and concludes that the comprehensive security approach provides a more nuanced and dynamic way of capturing the dynamic cooperative and competitive narratives of Arctic security today.